2020
DOI: 10.13057/biodiv/d211115
|View full text |Cite
|
Sign up to set email alerts
|

New emerging entomopathogenic fungi isolated from soil in South Sumatra (Indonesia) and their filtrate and conidial insecticidal activity against Spodoptera litura

Abstract: Abstract. Herlinda S, Efendi RA, Suharjo R, Hasbi, Setiawan A, Elfita, Verawaty M. 2020. New emerging entomopathogenic fungi isolated from soil in South Sumatra (Indonesia) and their filtrate and conidial insecticidal activity against Spodoptera litura. Biodiversitas 21: 5102-5113. This study was carried out to confirm identity of Beauveria bassiana and Metarhizium anisopliae using sequence analysis of Internal Transcribed Spacer (ITS) region as well as the two unknown isolates of EPF and to investigate their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
4
10
0
1
Order By: Relevance
“…(Figure 8). This is in accordance with the opinion of Barnett (1960), Sari and Rosmaita (2020), Herlinda et al (2020), that Beauveria has branched, insulated, hyaline and thick hyphae. Then the conidia are round or oval, one-celled, formed solitary at the tip of the conidiophores and attached to the short sterigma with alternating growth patterns (zig zag).…”
Section: Discussionsupporting
confidence: 92%
“…(Figure 8). This is in accordance with the opinion of Barnett (1960), Sari and Rosmaita (2020), Herlinda et al (2020), that Beauveria has branched, insulated, hyaline and thick hyphae. Then the conidia are round or oval, one-celled, formed solitary at the tip of the conidiophores and attached to the short sterigma with alternating growth patterns (zig zag).…”
Section: Discussionsupporting
confidence: 92%
“…aegypti eggs, larvae, and adults. The results of previous studies have proven that the species of entomopathogenic fungi from Indonesia could kill (80−100% mortality) several insect species of agricultural pests are B. bassiana (Sumikarsih et al 2019), M. anisopliae (Herlinda et al 2020b), Curvularia lunata (Herlinda et al 2021), Penicillium citrinum, and Talaromyces diversus (Herlinda et al 2020a). In this study, fungi from South Sumatra (Indonesia) were identified morphologically and molecularly, and their pathogenicity to egg, larvae, and adult Ae.…”
Section: Introductionmentioning
confidence: 84%
“…Another control method that has not shown resistance is the use of the entomopathogenic fungi (fungi causing disease in insects). The entomopathogenic fungi that have been shown to be effective at killing the insect pests of the genus Spodoptera are Beauveria bassiana, Metarhizium anisopliae (Ayudya et al 2019;Gustianingtyas et al 2020), Penicillium citrinum, and Talaromyces diversus (Herlinda et al 2020a). S. frugiperda was also killed by B. bassiana, M. anisopliae, Metarhizium rileyi (Ramanujam et al 2020), and Metarhizium spp.…”
Section: Introductionmentioning
confidence: 99%